Agricultural sector performance in Malawi - Matchaya, Greenwell C.; Nhlengethwa, Sibusiso; Chilonda, Pius (2014)
This paper charts the performance of the agriculture sector in Malawi for the period 2000 – 2013 (with particular attention paid to the last three to four years of the said period). In the quest to attain this aim the paper empirically focuses on the significance of mapping the performance of the sector in the form of trends against the baseline sectoral performance targets enlisted in the ASWAP, CAADP Framework and SADC RISDP. The consistent and concerted efforts by the Government of Malawi and development partners to meet the ASWAP, CAADP framework and SADC RISDP targets have resulted in the country making commendable economic growth and poverty alleviation. The country has been able to attain the 6% agricultural growth target despite the questionable quality of public expenditure. It is also interesting to note that changes in the agriculture sector appear to have had influence on incomes, poverty and malnourishment. The trend analysis led to the following findings; the growth in agricultural GDP and the annual GDP growth of the country surpassed the CAADP target of 6% annual growth and this culminated to an increase in production (cereal and livestock production) and productivity (land productivity) despite the fact that the country has not met the irrigation and fertiliser used targets. This increase in production and productivity may be earnestly attributed substantially public invested in the agriculture sector to meet the CAADP 10% target of the total budget to agriculture. However, this increase in agricultural GDP annual growth has not had a significant bearing on the country’s battle to offset poverty; the country’s GHI is still serious and the proportion of the population below the minimum dietary energy consumption is still high (23% on average) whilst the MDG I target stands at 20%. The major deduction from these findings is that there is a need for more concerted efforts in Malawi to refine agricultural growth investments; this can be carried out efficiently by developing a National Agriculture Plan (NAP) which will be a single policy tool that will guide investment and implementation of priorities in the sector.